Accretion and core formation: constraints from metal-silicate partitioning. - Wood, B (2008)
Experimental metal-silicate partitioning data for Ni, Co, V, Cr, Nb, Mn, Si and W were used to investigate the geochemical consequences of a range of models for accretion and core formation on Earth. The starting assumptions were chondritic ratios of refractory elements in the Earth and the segregation of metal at the bottom of a magma ocean, which deepened as the planet grew and which had, at its base, a temperature close to the liquidus of the silicate. The models examined were as follows. (i) Continuous segregation from a mantle which is chemically homogeneous and which has a fixed oxidation state, corresponding to 6.26 per cent oxidized Fe. Although Ni, Co and W partitioning is consistent with chondritic ratios, the current V content of the silicate Earth cannot be reconciled with core segregation under these conditions of fixed oxidation state. (ii) Continuous segregation from a mantle which is chemically homogeneous but in which the Earth became more oxidized as it grew. In this case, the Ni, Co, W, V, Cr and Nb contents of core and mantle are easily matched to those calculated from the chondritic ratios of refractory elements. The magma ocean is calculated to maintain a thickness approximately 35 per cent of the depth to the core-mantle boundary in the accreting Earth, yielding a maximum pressure of 44GPa. This model yields a Si content of the core of 5.7 per cent, in good agreement with cosmochemical estimates and with recent isotopic data. (iii) Continuous segregation from a mantle which is not homogeneous and in which the core equilibrates with a restricted volume of mantle at the base of the magma ocean. This is found to increase depth of the magma ocean by approximately 50 per cent. All of the other elements (except Mn) have partitioning consistent with chondritic abundances in the Earth, provided the Earth became, as before, progressively oxidized during accretion. (iv) Continuous segregation of metal from a crystal-melt mush. In this case, pressures decrease to a maximum of 31GPa and it is extremely difficult to match the calculated mantle contents of the highly incompatible elements Nb and W to those observed. Progressive oxidation is required to fit the observed mantle contents of vanadium. All of the scenarios discussed above point to progressive oxidation having occurred as the Earth grew. The Earth appears to be depleted in Mn relative to the chondritic reference.